Perjanjian Hudaybiyyah Dalam Prespektif Ralp Dahrendorf - Moh. Khoirul Fatih dan Moh. Sahlul Khuluq (Program Studi Ilmu Al Quran dan Tafsir Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2021)
This paper seeks to investigate further about how the peace efforts of Muslims through the Hudaybiyah Agreement? What conflict resolution is offered in the agreement? As well as analyzing the hudaybiyah agreement within the framework of Ralph Dahrendorf's conflict resolution theory. The history of Islam shows that